Analysis of Seasonal Patterns of Atmospheric Water Vapour and Rainfall in East Kalimantan and North Kalimantan Using the Lomb–Scargle Periodogram Method - Agus Ariyanto; Eko Yuli Handoko; Putra Maulida (Departemen Teknik Geomatika ITS, 2026)
This study examines the seasonal trends of Precipitable Water Vapour (PWV) obtained from GNSS data (2021–2023) and decadal rainfall data from BMKG (2001–2020) in East and North Kalimantan, employing the Lomb–Scargle Periodogram (LSP) method. The findings indicate that PWV is mostly influenced by an equatorial semi-annual cycle (about 0.5 years), while precipitation typically adheres to a monsoonal annual pattern (around 1 year). The correlation between PWV and precipitation is not wholly linear, exhibiting significant local variability in coastal areas. The LSP approach is effective in identifying dominant frequencies, albeit it exhibits reduced sensitivity to non-stationary fluctuations in atmospheric signals.